DEVELOPMENT OF ARTICULATE STORYLINE LEARNING MEDIA IN IMPROVING LEARNING OUTCOMES OF STUDENTS OF CLASS XI SMAS KAMPUS NOMMENSEN PEMATANGSIANTAR - Harry Cristofel Simanjuntak; R. Mursid; Abdul Hamid K (RADJA PUBLIKA, 2025)
This study aims to develop an interactive learning medium based on Articulate Storyline to improve student learning outcomes in Economics for Grade XI at SMAS Nommensen Pematangsiantar Campus. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The procedure involved needs analysis, media design and development, expert validation, and individual, small-group, and large-group trials. Validation results indicated that the media was highly feasible, with scores of 88% from content experts, 91% from media experts, and 89% from instructional design experts. Teacher practicality tests showed a 95% score, indicating the media was easy to use and relevant. Student responses in individual, small-group, and large-group scores scored 88%, 90%, and 92%, respectively, suggesting the media was engaging and easy to understand. Data analysis revealed that the experimental class average score increased from 64.17 (pretest) to 85.42 (posttest), with an N-Gain of 0.59 (moderate to high category). In contrast, the control class only improved from 63.19 to 70.83, with an N-Gain of 0.21 (low category). The t-test showed a significant difference between the two classes (tcount = 8.152 > ttable = 2.030; Sig. = 0.0001 < 0.05). It can be concluded that the Articulate Storyline learning media is highly feasible, practical, and effective for teaching Economics. This study recommends the use of interactive media and teacher training as key strategies for digital learning in the modern era.